The effects of the ketone body beta-hydroxybutyrate on the neuronal transcriptome (Translation: The University of Toledo Journal of Medical Sciences, 2025)
The ketogenic diet is emerging as an effective therapeutic option for patients with neurological disorders. The diet results in metabolism of fatty acids to ketone bodies like ?-hydroxybutyrates (BHBs), which serve as an alternative fuel source for brain cells. However, the molecular effect of BHB on neurons is not well understood. We hypothesized that BHB administration will induce upregulation of energy metabolism-related processes in neurons. To assess the effect of BHB administration on the neuronal transcriptome, we reanalyzed a publicly available RNAseq dataset (GSE252513) using a bioinformatic “3-pod” approach. We conducted pathway analysis and identified leading edge genes using Gene Set Enrichment Analysis (GSEA) and conducted chemical perturbagen analysis using the iLINCS repository to identify drugs that are concordant and discordant with BHB administration. We identified significantly altered (p
Keywords: Neuron; transcriptome; ketone body